Genetic alterations of m6A regulators predict poorer survival in acute myeloid leukemia. Issue 1 (December 2017) - Kwok, Chau-To; Marshall, Amy; Rasko, John; Wong, Justin
Abstract Methylation of N6 adenosine (m6 A) is known to be important for diverse biological processes including gene expression control, translation of protein, and messenger RNA (mRNA) splicing. However, its role in the development of human cancers is poorly understood. By analyzing datasets from the Cancer Genome Atlas Research Network (TCGA) acute myeloid leukemia (AML) study, we discover that mutations and/or copy number variations of m6 A regulatory genes are strongly associated with the presence of TP53 mutations in AML patients. Further, our analyses reveal that alterations in m6 A regulatory genes confer a worse survival in AML. Our work indicates that genetic alterations of m6 A regulatory genes may cooperate with TP53 and/or its regulator/downstream targets in the pathogenesis and/or maintenance of AML.